Investigating the COVID-19 related behaviors in the public transport system - Fatemeh Bakhtari Aghdam; Homayoun Sadeghi-Bazargani; Kavous Shahsavarinia; Fatemeh Jafari; Leila Jahangiry; Neda Gilani (BMC, 2021)
Abstract Background Determining people's healthy behaviors related to COVID-19 could be effective in providing preventive measures. The present study aims to investigate preventive behaviors associated with COVID-19 including wearing masks and keeping physical distance among the passengers on buses and public taxis measures to evaluate the ventilation systems in these vehicles. Methods This cross-sectional study was performed on 753 passengers on buses and taxis in Tabriz, northwestern Iran, from 15 February to 1 March 2021. Multistage sampling method was used to select the participants. Tabriz was socioeconomically divided into three areas, including high, moderate, and low socioeconomic status. Three researchers were observed passengers behaviors standing at the selected stations and assessed their behaviors according to study checklist. Results In total, the data were gathered from 358 (47.5%) female and 395 (52.5%) male in public transport systems. The results of this study indicated that female passengers used masks significantly more than men (P < 0.001). About 40% of men and women did not keep a physical distance of at least one meter in the public transportation system. Failing to keep social distancing was mostly observed among people with low SES (N = 103, 54%) and those who were in city center (N = 88, 48.5%). According to the multivariate regression analysis, for not wearing mask: being male [OR 4.94; 95%CI (2.62-9.28)] and using bus [(OR 3.27, 95%CI (1.73,6.19)], and for not physical distancing: having age under 25 years [OR 2.58; 95%CI (1.53,4.36)] and low socioeconomic status (SES) [OR 5.19; 95%CI (3.25,8.30)], and for no ventilation: using bus [OR 1.57; 95%CI (1.05,2.34)] were significant predictors. Conclusion Our results suggest that gender, type of vehicle, age, and SES were significant predictors of non-adherence to COVID-19 preventive behaviors in public transport during the pandemic. Given that social distancing is less observed in the public transportation system in Tabriz, Iran, it is necessary for government to consider and monitor guidelines to protect the passengers from COVID-19 infections by providing measures to maintain physical distance in public transportation systems. It may be possible to force vehicle owners who do not comply with health protocols to keep some distance by imposing fines.